Taos moderns : art of the new - Witt, David L. (Red Crane Books Santa Fe, New Mexico, 1992)
"This study focuses on those artists who created a substantial body of work in Taos between the mid-1940s and the early 1960s. Sixty or more artists who identified themselves as modernists, or as being influenced by modernism in art, lived in Taos during this period. A representative group of them are featured in this book"
65386
Keywords: Art, American -- Taos, New Mexico; Art, Modern -- 20th century -- Taos, New Mexico; Artist -- Biography -- Taos, New Mexico